Tb cotrol In India In the Covid era (2020)
The COVID-19 pandemic caused by the novel corona virus, severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), has upset the major public health care system throughout the world. Globally, by 3rd July 2020, there have been 10,719,946 confirmed cases of COVID-19, including 517,337 deaths, reported to WHO. In India, from Jan 30th to 3rd July 2020, there have been 625,544 confirmed cases of COVID-19 with 18,213 deaths (1). The COVID 19 pandemic has placed unprecedented demands and pressure on the health system. Health facilities and workforce are diverted and assigned a wide variety of activities related to controlling the outbreak. In doing so, other essential health services would be severely compromised. It is likely that seeking health care may be deferred because of social/physical distancing requirements or community reluctance owing to perceptions that health facilities may be infected., Continuing to provide essential services, while focusing on COVID 19 related activities, is important not only to maintain people’s trust in the health care delivery system (2), but also to minimize an increase in morbidity and mortality from other health conditions. During the Ebola outbreak in 2014-15, increased number of deaths was caused by measles, malaria, HIV/AIDS and tuberculosis because of failure in the health system and that exceeded deaths from Ebola itself (3, 4). Prevention and treatment services for noncommunicable diseases (NCDs) are affected severely since the pandemic began. A WHO survey completed by 155 countries during a 3-week period in May 2020, confirmed that the impact is global, but low-income countries are the most affected (5). More than half (53%) of the countries surveyed have partially or completely disrupted services for hypertension treatment; 49% for treatment for diabetes and diabetes-related complications; 42% for cancer treatment, and 31% for cardiovascular emergencies.